DOCUMENT VERSION CONTROL METHOD - TSUKUDA TAKAHIRO (1994)
PURPOSE:To attain the highly efficient control of document version by controlling the version number of the quoted original document in a document editing state based on a quotation table prepared in a document control system. CONSTITUTION:In a document editing system 2, the entry is applied to a quotation table 1A every time the quotation of a document is instructed during an editing job. At the same time, the present version is set at the latest one and the precedent one. When the system 2 reads the produced document out of a data base 3 as an editing subject, the table 1A is also read and the present version of the quoted original document is acquired from a document control system 1. At the same time, the present version number is set at the latest one of the table entry. The system 2 displays the contents of the precedent version for the quoted area where the version is changed when a person in charge instructs the display of the version change. When the document version is updated, the system 2 sets the latest or precedent version of the quoted area at a fixed version number of the table 1A and preserves the fixed version number as the present version.